Potential impact/effect of alcohol abuse on human development: a theoretical approach - A. Ndifon, Mary; S. Adiaha, Monday (SPC Journal of Education, 2018)
A theoretical survey on the potential impact/effect of alcohol abuse on human development was carried-out. The impact of alcohol abuse on the victims has being proven negative, with consequences like health challenges, financial challenges including societal challenges being identified as factors dragging the society towards ruin.Â Â